El problema de la auto-percepción de la multiplicidad en la unidad en Monadología - Paolucci, Mariela (2014)
Both a priori and a posteriori arguments concerning the existence of monads are taken into account to show the rejection of the thesis of substancial dualism, and regarding the major problem of a science of the individual.